Green and odor-free formaldehyde scavenger and preparation method thereof
By loading nano-FeAgZn alloys and nano-titanium dioxide in porous non-metallic minerals, FeAgZn/TiO2 photocatalysts are solved, and the problem that nano-titanium dioxide photocatalysts can only be excited by ultraviolet light is achieved, achieving efficient formaldehyde removal and odor cleaning effect under visible light.
Patent Information
- Application Number
- CN202510481344.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-07-08
AI Technical Summary
Existing nanotitanium dioxide photocatalysts can only be excited by ultraviolet light, resulting in low visible light utilization and low formaldehyde removal rate.
The nano-FeAgZn alloy is loaded in porous non-metallic minerals and then nano-titanium dioxide to form FeAgZn/TiO2 photocatalyst, which promotes the efficient absorption of light energy in visible light and enhances the photocatalyst.
Under visible light conditions, formaldehyde scavenger has excellent formaldehyde removal capabilities and improves the odor cleansing effect through the physical adsorption capacity of porous non-metallic minerals, which is suitable for a variety of scenarios.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of formaldehyde scavengers, and particularly relates to a green odor-removing formaldehyde scavenger and a preparation method thereof. Background Art
[0002] As an air purification product, an odor-removing formaldehyde scavenger catalyzes and oxidizes formaldehyde into harmless carbon dioxide and water by loading photocatalysts, plant extracts, etc., avoiding secondary pollution and eliminating odors. While removing formaldehyde, the odor-removing formaldehyde scavenger itself also needs to be more green and safe, which requires no harmful substances such as chlorine and benzene, a pH value tending to be neutral, and no corrosion to household surfaces, and is suitable for various scenarios such as boards, wallpapers, and fabrics.
[0003] At present, some green odor-removing formaldehyde scavengers generally use inorganic adsorption materials as the main materials, on which photocatalyst materials such as nano-titanium dioxide are loaded to generate active oxygen under light irradiation to continuously decompose formaldehyde; and the added plant extracts are used to neutralize the decoration odors to achieve long-term air purification. However, general nano-titanium dioxide photocatalysts can only be excited by ultraviolet light, and the utilization rate of visible light is low, resulting in a low formaldehyde removal rate. Summary of the Invention
[0004] The purpose of the present invention is to provide a green odor-removing formaldehyde scavenger and a preparation method thereof. The prepared formaldehyde scavenger has excellent formaldehyde removal rate, is green and safe, and is suitable for application in various scenarios.
[0005] To achieve the above purpose, the present invention is realized through the following technical solutions: A preparation method of a green odor-removing formaldehyde scavenger, comprising the following steps: (1) Add ethanol, Fe salt, Ag salt, Zn salt, and ascorbic acid to a reaction kettle, stir and disperse to obtain a metal precursor ethanol mixture, then add porous non-metallic ore materials, seal the reaction kettle, and heat to 230-260 °C, keep warm for 10-18 h, then cool to room temperature and filter, wash, and dry to obtain porous non-metallic ore materials loaded with FeAgZn; (2) Place the porous non-metallic ore materials loaded with FeAgZn in an aqueous sodium hydroxide solution, heat to 60-70 °C, and then add an aqueous titanium tetrachloride solution while stirring; after adding, continue to stir for 4-6 h, then filter, wash, and dry to obtain porous non-metallic ore materials loaded with FeAgZn / TiO2 photocatalyst; (3) Immerse the porous non-metallic ore materials loaded with FeAgZn / TiO2 photocatalyst in a natural plant fragrance ethanol solution, then filter and dry to obtain the formaldehyde scavenger.
[0006] Preferably, in step (1), the molar ratio of the Fe salt, Ag salt, and Zn salt is 0.5-1:0.5-1:0.5-1.
[0007] Preferably, in step (1), in the metal precursor ethanol mixture, the total mass fraction of the Fe salt, Ag salt, and Zn salt is 3.5-6%, and the mass fraction of ascorbic acid is 3-6%; the mass ratio of the metal precursor ethanol mixture to the porous non-metallic ore material is 10:0.7-1.2.
[0008] Preferably, in step (1), the porous non-metallic ore material is one of porous diatomite, porous zeolite, and porous bentonite.
[0009] Preferably, in step (1), the preparation method of the porous non-metallic ore material includes the following steps: Immerse the non-metallic ore material powder in hydrochloric acid with a mass fraction of 3-6% for 12-18 h, then wash and dry it to obtain the pretreated non-metallic ore material powder; the non-metallic ore material powder is one of diatomite, zeolite, and bentonite; Then add an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose to the pretreated non-metallic ore material powder, ball-mill and mix it, first conduct vacuum drying at 60-65 °C, then place it in a roasting furnace for roasting, and then cool it to room temperature with the furnace, and obtain the porous non-metallic ore material after crushing.
[0010] Preferably, the mass ratio of the non-metallic ore material powder to the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose is 1:2-3; in the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol is 15-20%, the molecular weight of polyethylene glycol is 5000-10000, the mass fraction of urea is 3-5%, and the mass fraction of sodium carboxymethylcellulose is 1-2%.
[0011] Preferably, during the roasting, first raise the temperature to 150-170 °C for roasting for 20-40 min, then raise the temperature to 230-270 °C for roasting for 20-40 min, and then raise the temperature to 400-420 °C for roasting for 50-80 min.
[0012] Preferably, in step (2), the concentration of the titanium tetrachloride aqueous solution is 0.6-1 mol / L; the concentration of the sodium hydroxide aqueous solution is 1.5-2 mol / L; the molar ratio of titanium tetrachloride in the added titanium tetrachloride aqueous solution to sodium hydroxide in the sodium hydroxide aqueous solution is 0.5-0.9:1; the mass ratio of the porous non-metallic ore material loaded with FeAgZn to the sodium hydroxide aqueous solution is 1:15-25; the temperature of the titanium tetrachloride aqueous solution is maintained between 2-4 °C.
[0013] Preferably, in step (3), the mass fraction of the natural plant spice ethanol solution is 10-20%, and the natural plant spice is one or more of peppermint essential oil, lavender essential oil, wormwood essential oil, eucalyptus essential oil, rose essential oil, clove essential oil, and lemon essential oil; the impregnation time is 2-5 h.
[0014] As a general inventive concept, the present invention provides a green odor-removing formaldehyde scavenger prepared by the above preparation method.
[0015] The beneficial effects of the present invention are as follows: 1. When preparing the formaldehyde scavenger of the present invention, nano-FeAgZn alloy is first loaded in the porous non-metallic ore, and then nano-titanium dioxide is loaded, so that the porous non-metallic ore is loaded with FeAgZn / TiO2 photocatalyst. Among them, the nano-FeAgZn alloy, as a photosensitizer, can promote the absorption of visible light by nano-TiO2 and enhance the light absorption in the visible light region, so that nano-TiO2 has a high photocatalytic effect under visible light, and further enables the formaldehyde scavenger to have excellent formaldehyde removal ability under visible light conditions. Among them, when preparing the formaldehyde scavenger of the present invention, loading nano-FeAgZn alloy in the porous non-metallic ore can make the aldehyde scavenger show better formaldehyde removal ability compared with loading nano-Fe, nano-Ag, nano-FeAg alloy, etc.
[0016] 2. When preparing the porous non-metallic ore of the present invention, polyethylene glycol and urea with appropriate molecular weights are used as the main pore-forming agents and combined with an appropriate calcination process, so that the obtained porous non-metallic ore has stable and uniform pores, which can not only improve the loading effect of the FeAgZn / TiO2 photocatalyst, but also enhance its physical adsorption ability and facilitate the diffusion and adsorption of formaldehyde molecules inside the material, thereby improving the formaldehyde removal ability. Moreover, the porous non-metallic ore in the present invention has a strong loading capacity for natural plant spices, which can make the formaldehyde scavenger show excellent odor-removing effects.
[0017] 3. The formaldehyde scavenger in the present invention is green and safe and is suitable for application in various scenarios. Specific embodiments
[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0019] Example 1: A preparation method of a green odorless formaldehyde scavenger, comprising the following steps: (1) Add ethanol, iron nitrate, silver nitrate, zinc nitrate, and ascorbic acid to a reaction kettle. After stirring and dispersing, a metal precursor ethanol mixture is obtained; in the metal precursor ethanol mixture, the total mass fraction of iron nitrate, silver nitrate, and zinc nitrate is 5%, and the mass fraction of ascorbic acid is 5%; the molar ratio of iron nitrate, silver nitrate, and zinc nitrate is 1:1:1; Then add porous diatomite, and the mass ratio of the metal precursor ethanol mixture to the porous diatomite is 10:1; seal the reaction kettle, heat it to 260 °C, keep it warm for 12 h, then cool it to room temperature and filter, wash, and dry to obtain porous diatomite supported FeAgZn; Among them, the preparation method of the porous diatomite includes the following steps: Soak diatomite powder in hydrochloric acid with a mass fraction of 5% for 15 h, then wash it with water and dry it to obtain pretreated diatomite powder; then add an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose with 3 times its mass to the pretreated diatomite powder, ball-mill and mix, first perform vacuum drying at 65 °C, then place it in a roasting furnace for roasting. When roasting, first heat it to 155 °C and roast for 30 min, then heat it to 240 °C and roast for 30 min, and then heat it to 420 °C and roast for 60 min; then cool it to room temperature with the furnace and pulverize to obtain porous diatomite.
[0020] Among them, in the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol is 18%, the molecular weight of polyethylene glycol is 8000, the mass fraction of urea is 5%, and the mass fraction of sodium carboxymethylcellulose is 1.5%.
[0021] (2) Place the porous diatomite supported FeAgZn in an aqueous sodium hydroxide solution with a concentration of 2 mol / L, heat it to 65 °C, and then add an aqueous titanium tetrachloride solution with a temperature maintained between 2 and 4 °C and a concentration of 0.8 mol / L while stirring; after adding, continue to stir for 6 h, then filter, wash, and dry to obtain a porous diatomite supported FeAgZn / TiO2 photocatalyst; Among them, the mass ratio of the porous diatomite supported FeAgZn to the aqueous sodium hydroxide solution is 1:20; the molar ratio of titanium tetrachloride in the added aqueous titanium tetrachloride solution to sodium hydroxide in the aqueous sodium hydroxide solution is 0.7:1.
[0022] (3) Immerse the porous diatomite supported FeAgZn / TiO2 photocatalyst in a lemon essential oil ethanol solution with a mass fraction of 15% for 3 h, then filter and dry to obtain the formaldehyde scavenger.
[0023] Example 2: A preparation method of a green odorless formaldehyde scavenger, comprising the following steps: (1) Add ethanol, iron nitrate, silver nitrate, zinc nitrate, and ascorbic acid to a reaction kettle. After stirring and dispersing, a metal precursor ethanol mixed solution is obtained; in the metal precursor ethanol mixed solution, the total mass fraction of iron nitrate, silver nitrate, and zinc nitrate is 3.5%, and the mass fraction of ascorbic acid is 3%; the molar ratio of iron nitrate, silver nitrate, and zinc nitrate is 1:1:1; Then add porous diatomite, and the mass ratio of the metal precursor ethanol mixed solution to the porous diatomite is 10:0.8; seal the reaction kettle, heat it up to 230 °C, keep it warm for 12 h, then cool it to room temperature and filter, wash, and dry to obtain porous diatomite supported FeAgZn; Among them, the preparation method of the porous diatomite comprises the following steps: Soak diatomite powder in hydrochloric acid with a mass fraction of 5% for 15 h, then wash it with water and dry it to obtain pretreated diatomite powder; then add an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose with 3 times its mass to the pretreated diatomite powder, ball-mill and mix, first conduct vacuum drying at 60 °C, then place it in a roasting furnace for roasting. When roasting, first heat it up to 155 °C and roast for 40 min, then heat it up to 250 °C and roast for 30 min, and then heat it up to 410 °C and roast for 60 min; then cool it to room temperature with the furnace and crush it to obtain porous diatomite; Among them, in the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol is 15%, the molecular weight of polyethylene glycol is 8000, the mass fraction of urea is 4%, and the mass fraction of sodium carboxymethylcellulose is 1.5%.
[0024] (2) Place the porous diatomite supported FeAgZn in an aqueous sodium hydroxide solution with a concentration of 2 mol / L, heat it up to 65 °C, and then while stirring, add an aqueous titanium tetrachloride solution with a temperature maintained between 2 and 4 °C and a concentration of 0.6 mol / L; after adding, continue to stir for 6 h, then filter, wash, and dry to obtain a porous diatomite supported FeAgZn / TiO2 photocatalyst; Among them, the mass ratio of the porous diatomite supported FeAgZn to the aqueous sodium hydroxide solution is 1:18; the molar ratio of titanium tetrachloride in the added aqueous titanium tetrachloride solution to sodium hydroxide in the aqueous sodium hydroxide solution is 0.6:1.
[0025] (3) Immerse the porous diatomite supported FeAgZn / TiO2 photocatalyst in a 20% lemon essential oil ethanol solution for 2 h, then filter and dry to obtain the formaldehyde scavenger.
[0026] Example 3: A preparation method of a green odorless formaldehyde scavenger, comprising the following steps: (1) Add ethanol, iron nitrate, silver nitrate, zinc nitrate, and ascorbic acid into a reaction kettle. After stirring and dispersing, a metal precursor ethanol mixed solution is obtained; in the metal precursor ethanol mixed solution, the total mass fraction of iron nitrate, silver nitrate, and zinc nitrate is 6%, and the mass fraction of ascorbic acid is 6%; the molar ratio of iron nitrate, silver nitrate, and zinc nitrate is 1:1:0.5; Then add porous diatomite, and the mass ratio of the metal precursor ethanol mixed solution to the porous diatomite is 10:0.7; seal the reaction kettle, heat it up to 230 °C, keep it warm for 18 h, then cool it to room temperature and filter, wash, and dry to obtain porous diatomite supported FeAgZn; Among them, the preparation method of the porous diatomite comprises the following steps: Soak diatomite powder in hydrochloric acid with a mass fraction of 5% for 18 h, then wash it with water and dry it to obtain pretreated diatomite powder; then add an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose with a mass three times that of the pretreated diatomite powder, ball-mill and mix, first perform vacuum drying at 60 °C, and then place it in a roasting furnace for roasting. When roasting, first heat it up to 150 °C and roast for 20 min, then heat it up to 230 °C and roast for 40 min, and then heat it up to 420 °C and roast for 60 min; then cool it to room temperature with the furnace and crush it to obtain porous diatomite; Among them, in the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol is 20%, the molecular weight of polyethylene glycol is 8000, the mass fraction of urea is 4%, and the mass fraction of sodium carboxymethylcellulose is 1.5%.
[0027] (2) Place the porous diatomite supported FeAgZn in an aqueous sodium hydroxide solution with a concentration of 1.5 mol / L, heat it up to 60 °C, and then add an aqueous titanium tetrachloride solution with a temperature maintained between 2 and 4 °C and a concentration of 0.6 mol / L while stirring; after adding, continue to stir for 6 h, then filter, wash, and dry to obtain a porous diatomite supported FeAgZn / TiO₂ photocatalyst; Among them, the mass ratio of the porous diatomite supported FeAgZn to the aqueous sodium hydroxide solution is 1:25; the molar ratio of titanium tetrachloride in the added aqueous titanium tetrachloride solution to sodium hydroxide in the aqueous sodium hydroxide solution is 0.5:1.
[0028] (3) Immerse the porous diatomite supported FeAgZn / TiO₂ photocatalyst in a 20% lemon essential oil ethanol solution for 2 h, then filter and dry to obtain the formaldehyde scavenger.
[0029] Example 4: A preparation method of a green odorless formaldehyde scavenger, comprising the following steps: (1) Add ethanol, iron nitrate, silver nitrate, zinc nitrate, and ascorbic acid to a reaction kettle. After stirring and dispersing, a metal precursor ethanol mixture is obtained; in the metal precursor ethanol mixture, the total mass fraction of iron nitrate, silver nitrate, and zinc nitrate is 4.5%, and the mass fraction of ascorbic acid is 4%; the molar ratio of iron nitrate, silver nitrate, and zinc nitrate is 1:0.5:0.5; Then add porous zeolite, and the mass ratio of the metal precursor ethanol mixture to the porous zeolite is 10:1.2; seal the reaction kettle, heat it to 245 °C, keep it warm for 15 h, then cool it to room temperature and filter, wash, and dry to obtain porous zeolite supported FeAgZn; Among them, the preparation method of the porous zeolite includes the following steps: Soak zeolite powder in hydrochloric acid with a mass fraction of 5% for 12 h, then wash with water and dry to obtain pretreated zeolite powder; then add an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose with twice its mass to the pretreated zeolite powder, ball-mill and mix, first perform vacuum drying at 65 °C, and then place it in a roasting furnace for roasting. When roasting, first heat it to 160 °C and roast for 40 min, then heat it to 240 °C and roast for 40 min, and then heat it to 420 °C and roast for 50 min; then cool it to room temperature with the furnace and crush it to obtain porous zeolite; Among them, in the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol is 18%, the molecular weight of polyethylene glycol is 8000, the mass fraction of urea is 5%, and the mass fraction of sodium carboxymethylcellulose is 2%.
[0030] (2) Place the porous zeolite supported FeAgZn in an aqueous sodium hydroxide solution with a concentration of 2 mol / L, heat it to 65 °C, and then add an aqueous titanium tetrachloride solution with a temperature maintained between 2 and 4 °C and a concentration of 1 mol / L while stirring; after adding, continue to stir for 4 h, then filter, wash, and dry to obtain a porous zeolite supported FeAgZn / TiO₂ photocatalyst; Among them, the mass ratio of the porous zeolite supported FeAgZn to the aqueous sodium hydroxide solution is 1:15; the molar ratio of titanium tetrachloride in the added aqueous titanium tetrachloride solution to sodium hydroxide in the aqueous sodium hydroxide solution is 0.9:1.
[0031] (3) Immerse the porous zeolite supported FeAgZn / TiO₂ photocatalyst in a 10% lemon essential oil ethanol solution for 5 h, then filter and dry to obtain the formaldehyde scavenger.
[0032] Example 5: A preparation method of a green odorless formaldehyde scavenger, comprising the following steps: (1) Add ethanol, iron nitrate, silver nitrate, zinc nitrate, and ascorbic acid to a reaction kettle. After stirring and dispersing, a metal precursor ethanol mixture is obtained; in the metal precursor ethanol mixture, the total mass fraction of iron nitrate, silver nitrate, and zinc nitrate is 3.5%, and the mass fraction of ascorbic acid is 4.5%; the molar ratio of iron nitrate, silver nitrate, and zinc nitrate is 1:1:1; Then add porous diatomite, and the mass ratio of the metal precursor ethanol mixture to the porous diatomite is 10:1; seal the reaction kettle, heat it up to 260 °C, keep it warm for 10 h, then cool it to room temperature and filter, wash, and dry to obtain porous diatomite supported FeAgZn; Among them, the preparation method of the porous diatomite includes the following steps: Soak diatomite powder in hydrochloric acid with a mass fraction of 5% for 15 h, then wash with water and dry to obtain pretreated diatomite powder; then add an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose with a mass 2.5 times that of the pretreated diatomite powder, ball-mill and mix, first perform vacuum drying at 62 °C, then place it in a roasting furnace for roasting. When roasting, first heat up to 170 °C and roast for 30 min, then heat up to 270 °C and roast for 20 min, and then heat up to 400 °C and roast for 80 min; then cool it to room temperature with the furnace and pulverize to obtain porous diatomite; Among them, in the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol is 15%, the molecular weight of polyethylene glycol is 8000, the mass fraction of urea is 3%, and the mass fraction of sodium carboxymethylcellulose is 1%.
[0033] (2) Place the porous diatomite supported FeAgZn in an aqueous sodium hydroxide solution with a concentration of 1.8 mol / L, heat it up to 70 °C, and then add an aqueous titanium tetrachloride solution with a temperature maintained between 2 and 4 °C and a concentration of 0.8 mol / L while stirring; after adding, continue to stir for 5 h, then filter, wash, and dry to obtain a porous diatomite supported FeAgZn / TiO₂ photocatalyst; Among them, the mass ratio of the porous diatomite supported FeAgZn to the aqueous sodium hydroxide solution is 1:22; the molar ratio of titanium tetrachloride in the added aqueous titanium tetrachloride solution to sodium hydroxide in the aqueous sodium hydroxide solution is 0.8:1.
[0034] (3) Immerse the porous diatomite supported FeAgZn / TiO₂ photocatalyst in a lemon essential oil ethanol solution with a mass fraction of 16% for 3 h, then filter and dry to obtain the formaldehyde scavenger.
[0035] Comparative Example 1: A preparation method of a green odorless formaldehyde scavenger, which is different from Example 5 in that FeAgZn is not loaded on the porous diatomite. The preparation method of the formaldehyde scavenger specifically includes the following steps: (1) Preparation of porous diatomite: Soak diatomite powder in hydrochloric acid with a mass fraction of 5% for 15 h, then wash with water and dry to obtain pretreated diatomite powder; then add an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, which is 2.5 times the mass of the pretreated diatomite powder, and mix by ball milling. First, conduct vacuum drying at 62 °C, and then place it in a roasting furnace for roasting. When roasting, first raise the temperature to 170 °C and roast for 30 min, then raise the temperature to 270 °C and roast for 20 min, and then raise the temperature to 400 °C and roast for 80 min; then cool with the furnace to room temperature and crush to obtain porous diatomite; Among the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol is 15%, the molecular weight of polyethylene glycol is 8000, the mass fraction of urea is 3%, and the mass fraction of sodium carboxymethylcellulose is 1%.
[0036] (2) Place the porous diatomite in an aqueous sodium hydroxide solution with a concentration of 1.8 mol / L, raise the temperature to 70 °C, and then add an aqueous titanium tetrachloride solution with a temperature maintained between 2 and 4 °C and a concentration of 0.8 mol / L while stirring; after adding, continue to stir for 5 h, then filter, wash, and dry to obtain porous diatomite supported TiO₂ photocatalyst; Among them, the mass ratio of porous diatomite to the aqueous sodium hydroxide solution is 1:22; the molar ratio of titanium tetrachloride in the added aqueous titanium tetrachloride solution to sodium hydroxide in the aqueous sodium hydroxide solution is 0.8:1.
[0037] (3) Immerse the porous diatomite supported TiO₂ photocatalyst in a lemon essential oil ethanol solution with a mass fraction of 16% for 3 h, then filter and dry to obtain the formaldehyde scavenger.
[0038] Comparative Example 2: A preparation method of a green odorless formaldehyde scavenger, which is different from Example 5 in that the porous diatomite supported FeAgZn is replaced with porous diatomite supported Ag; The preparation method of the porous diatomite supported Ag specifically includes the following steps: Add ethanol, silver nitrate, and ascorbic acid to the reaction kettle, stir and disperse to obtain a metal precursor ethanol mixed solution; in the metal precursor ethanol mixed solution, the mass fraction of silver nitrate is 3.5%, and the mass fraction of ascorbic acid is 4.5%; Then add porous diatomite, and the mass ratio of the metal precursor ethanol mixture to porous diatomite is 10:1; seal the reaction kettle, heat it up to 260 °C, keep it warm for 10 h, then cool it to room temperature and filter, wash, and dry to obtain Ag-loaded porous diatomite.
[0039] Comparative Example 3: A preparation method of a green odorless formaldehyde scavenger, which is different from Example 5 in that the FeAgZn-loaded porous diatomite is replaced by Fe-loaded porous diatomite; The preparation method of Fe-loaded porous diatomite specifically includes the following steps: Add ethanol, ferric nitrate, and ascorbic acid to the reaction kettle, stir and disperse to obtain a metal precursor ethanol mixture; in the metal precursor ethanol mixture, the mass fraction of ferric nitrate is 3.5%, and the mass fraction of ascorbic acid is 4.5%; Then add porous diatomite, and the mass ratio of the metal precursor ethanol mixture to porous diatomite is 10:1; seal the reaction kettle, heat it up to 260 °C, keep it warm for 10 h, then cool it to room temperature and filter, wash, and dry to obtain Fe-loaded porous diatomite.
[0040] Comparative Example 4: A preparation method of a green odorless formaldehyde scavenger, which is different from Example 5 in that the FeAgZn-loaded porous diatomite is replaced by FeAg-loaded porous diatomite; The preparation method of FeAg-loaded porous diatomite specifically includes the following steps: Add ethanol, ferric nitrate, silver nitrate, and ascorbic acid to the reaction kettle, stir and disperse to obtain a metal precursor ethanol mixture; in the metal precursor ethanol mixture, the total mass fraction of ferric nitrate and silver nitrate is 3.5%, and the mass fraction of ascorbic acid is 4.5%; the molar ratio of ferric nitrate to silver nitrate is 1:1; Then add porous diatomite, and the mass ratio of the metal precursor ethanol mixture to porous diatomite is 10:1; seal the reaction kettle, heat it up to 260 °C, keep it warm for 10 h, then cool it to room temperature and filter, wash, and dry to obtain FeAg-loaded porous diatomite.
[0041] Comparative Example 5: A preparation method of a green odorless formaldehyde scavenger, which is different from Example 5 in that the FeAgZn-loaded porous diatomite is replaced by FeAgNi-loaded porous diatomite; The preparation method of FeAgNi-loaded porous diatomite specifically includes the following steps: Ethanol, iron nitrate, silver nitrate, nickel nitrate, and ascorbic acid were added to the reaction kettle. After stirring and dispersing, a metal precursor ethanol mixture was obtained. In the metal precursor ethanol mixture, the total mass fraction of iron nitrate, silver nitrate, and zinc nitrate was 3.5%, and the mass fraction of ascorbic acid was 4.5%. The molar ratio of iron nitrate, silver nitrate, and nickel nitrate was 1:1:1. Then, porous diatomite was added, and the mass ratio of the metal precursor ethanol mixture to the porous diatomite was 10:1. The reaction kettle was sealed and heated to 260 °C, held for 10 h, then cooled to room temperature and filtered, washed, and dried to obtain FeAgNi supported on porous diatomite.
[0042] Comparative Example 6: A method for preparing a green odorless formaldehyde scavenger, which is different from Example 5 in that the preparation method of the porous diatomite includes the following steps: The diatomite powder was immersed in hydrochloric acid with a mass fraction of 5% for 15 h, then washed with water and dried to obtain pretreated diatomite powder. Then, an aqueous solution containing polyethylene glycol and sodium carboxymethylcellulose, which was 2.5 times the mass of the pretreated diatomite powder, was added. After ball milling and mixing, it was first vacuum dried at 62 °C, then placed in a roasting furnace for roasting. During roasting, it was first heated to 170 °C and roasted for 30 min, then heated to 270 °C and roasted for 20 min, and then heated to 400 °C and roasted for 80 min. Then, it was cooled to room temperature with the furnace and pulverized to obtain porous diatomite. Among them, in the aqueous solution containing polyethylene glycol and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol was 15%, the molecular weight of polyethylene glycol was 8000, and the mass fraction of sodium carboxymethylcellulose was 1%.
[0043] Comparative Example 7: A method for preparing a green odorless formaldehyde scavenger, which is different from Example 5 in that the preparation method of the porous diatomite includes the following steps: The diatomite powder was immersed in hydrochloric acid with a mass fraction of 5% for 15 h, then washed with water and dried to obtain pretreated diatomite powder. Then, an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, which was 2.5 times the mass of the pretreated diatomite powder, was added. After ball milling and mixing, it was first vacuum dried at 62 °C, then placed in a roasting furnace for roasting. During roasting, it was first heated to 170 °C and roasted for 30 min, then heated to 270 °C and roasted for 20 min, and then heated to 400 °C and roasted for 80 min. Then, it was cooled to room temperature with the furnace and pulverized to obtain porous diatomite. Among them, in the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol was 3%, the molecular weight of polyethylene glycol was 8000, the mass fraction of urea was 15%, and the mass fraction of sodium carboxymethylcellulose was 1%.
[0044] Performance test: Place the formaldehyde scavengers of Examples 1-5 and Comparative Examples 1-7 in an airtight test chamber with the formaldehyde content in the test chamber being 1±0.05 mg / m 3 , and the placement amount of the formaldehyde scavenger in the glass test chamber is 12 g / m 3 . Irradiate visible light on the test chamber. The visible light is artificially simulated visible light with an illumination intensity of 3.0×10 4 lx. Test the formaldehyde content in the test chamber at illumination times of 1 h, 10 h, and 20 h respectively, and calculate the corresponding formaldehyde removal rate. The specific test results of the removal rate are shown in Table 1.
[0045] Table 1 Test results of formaldehyde removal rate
[0046] As can be seen from Table 1, the formaldehyde scavenger in the embodiments of the present invention can quickly remove formaldehyde and has a high formaldehyde removal rate. By comparing Example 5 with Comparative Example 1, it can be seen that if no nano metal or nano alloy is loaded in the porous diatomite, the formaldehyde removal rate will be significantly reduced. By comparing Example 5 with Comparative Examples 2-5, loading the nano FeAgZn alloy in the porous non-metallic ore can make the formaldehyde scavenger exhibit better formaldehyde removal ability compared with loading nano Fe, nano Ag, nano FeAg alloy, nano FeAgNi alloy, etc. By comparing Example 5 with Comparative Example 6, using urea and polyethylene glycol in combination as the pore-forming agent for the porous diatomite can make the obtained formaldehyde scavenger have better formaldehyde removal performance compared with polyethylene glycol. By comparing Example 5 with Comparative Example 7, using urea and polyethylene glycol in combination as the pore-forming agent for the porous diatomite, if the addition amount of urea is relatively large while the addition amount of polyethylene glycol is significantly small, the formaldehyde removal performance of the obtained formaldehyde scavenger will be reduced.
[0047] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A preparation method of a green odorless formaldehyde scavenger, characterized in that, It includes the following steps: (1) Add ethanol, Fe salt, Ag salt, Zn salt, and ascorbic acid into a reaction kettle. After stirring and dispersing, a metal precursor ethanol mixture is obtained. Then add porous non-metallic ore material, seal the reaction kettle, and heat it to 230 - 260 °C, keep it warm for 10 - 18 h, then cool it to room temperature and filter, wash, and dry to obtain porous non-metallic ore material loaded with FeAgZn; (2) Place the porous non-metallic ore material loaded with FeAgZn in an aqueous sodium hydroxide solution, heat it to 60 - 70 °C, and then add an aqueous titanium tetrachloride solution while stirring; after adding, continue to stir for 4 - 6 h, then filter, wash, and dry to obtain a porous non-metallic ore material loaded with FeAgZn / TiO₂ photocatalyst; (3) Immerse the porous non-metallic ore material loaded with FeAgZn / TiO₂ photocatalyst in a natural plant fragrance ethanol solution, then filter and dry to obtain the formaldehyde scavenger.
2. The preparation method of the formaldehyde scavenger with green odor removal as claimed in claim 1, wherein, In step (1), the molar ratio of the Fe salt, Ag salt, and Zn salt is 0.5 - 1:0.5 - 1:0.5 - 1.
3. The preparation method of the green odorless formaldehyde scavenger according to claim 1, wherein, In step (1), in the metal precursor ethanol mixture, the total mass fraction of the Fe salt, Ag salt, and Zn salt is 3.5 - 6%, and the mass fraction of ascorbic acid is 3 - 6%; the mass ratio of the metal precursor ethanol mixture to the porous non-metallic ore material is 10:0.7 - 1.
2.
4. The preparation method of the formaldehyde scavenger with green odor removal as described in claim 1, characterized in that, In step (1), the porous non-metallic ore material is one of porous diatomite, porous zeolite, and porous bentonite.
5. The preparation method of the formaldehyde scavenger with green odor removal as claimed in claim 4, characterized in that, In step (1), the preparation method of the porous non-metallic ore material includes the following steps: Immerse the non-metallic ore material powder in hydrochloric acid with a mass fraction of 3 - 6% for 12 - 18 h, then wash with water and dry to obtain a pretreated non-metallic ore material powder; the non-metallic ore material powder is one of diatomite, zeolite, and bentonite; Then add an aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose to the pretreated non-metallic ore material powder, ball-mill and mix, first conduct vacuum drying at 60 - 65 °C, then place it in a roasting furnace for roasting, and then cool it to room temperature with the furnace, and obtain the porous non-metallic ore material after pulverization.
6. The preparation method of the formaldehyde scavenger with green odor removal as claimed in claim 5, characterized in that, The mass ratio of the non-metallic ore material powder to the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose is 1:2 - 3; in the aqueous solution containing polyethylene glycol, urea, and sodium carboxymethylcellulose, the mass fraction of polyethylene glycol is 15 - 20%, the molecular weight of polyethylene glycol is 5000 - 10000, the mass fraction of urea is 3 - 5%, and the mass fraction of sodium carboxymethylcellulose is 1 - 2%.
7. The preparation method of the formaldehyde scavenger with green odor removal as described in claim 5, characterized in that, During the roasting, first heat it to 150 - 170 °C for roasting for 20 - 40 min, then heat it to 230 - 270 °C for roasting for 20 - 40 min, and then heat it to 400 - 420 °C for roasting for 50 - 80 min.
8. The preparation method of the formaldehyde scavenger with green odor removal as described in claim 1, characterized in that, In step (2), the concentration of the titanium tetrachloride aqueous solution is 0.6 - 1 mol / L; the concentration of the sodium hydroxide aqueous solution is 1.5 - 2 mol / L; the molar ratio of titanium tetrachloride in the added titanium tetrachloride aqueous solution to sodium hydroxide in the sodium hydroxide aqueous solution is 0.5 - 0.9:1; the mass ratio of the porous non-metallic ore material loaded with FeAgZn to the sodium hydroxide aqueous solution is 1:15 - 25; the temperature of the titanium tetrachloride aqueous solution is maintained between 2 and 4 °C.
9. The preparation method of the formaldehyde scavenger with green odor removal as claimed in claim 1, characterized in that, In step (3), the mass fraction of the natural plant fragrance ethanol solution is 10 - 20%, and the natural plant fragrance is one or more of peppermint essential oil, lavender essential oil, wormwood essential oil, eucalyptus essential oil, rose essential oil, clove essential oil, and lemon essential oil; the impregnation time is 2 - 5 h.
10. A green odor-removing formaldehyde scavenger prepared by the preparation method according to any one of claims 1 to 9.